Development of smart blind stick using global positioning system - Hairol Anuar, Siti Haryanti; Mahadevan, Yamunaa (Media Applied Science and Engineering, 2024)
As technology becomes more and more integrated into daily life, especially for blind people. One of the tools for them is blind stick as an assistive device. It is designed to enhance the mobility and independence of visually impaired individuals. Traditional blind sticks provide basic obstacle detection and aid in navigation, but it lacks an advanced feature for precise location tracking and route guidance. This project aims to leverage the function of Global Positioning System (GPS) technology by developing a prototype of smart blind stick that can send information to the user's position and provide audio-based for alert. GPS modules as an Internet of Things (IoT) features acquire real-time coordinates alerts to the users and a microcontroller NODEMCU ESP8266 was used to process the data. To enhance the functionality, additional features of obstacle detection using ultrasonic sensors have been integrated. The sensor can alert the user about potential obstacles in their path, further improving safety during navigation. The smart blind stick using GPS aims to offer a cost-effective and efficient solution for visually impaired individuals, enabling them to navigate unfamiliar environments with confidence. The success of this project will be evaluated through simple user testing and feedback collection.